The Choice of Payment Method in European Mergers and Acquisitions - FACCIO, MARA; MASULIS, RONALD W. (Journal of Finance, 2005)
ABSTRACT We study merger and acquisition (M&A) payment choices of European bidders for publicly and privately held targets in the 1997–2000 period. Europe is an ideal venue for studying the importance of corporate governance in making M&A payment choices, given the large number of closely held firms and the wide range of capital markets, institutional settings, laws, and regulations. The tradeoff between corporate governance concerns and debt financing constraints is found to have a large bearing on the bidder's payment choice. Consistent with earlier evidence, we find that several deal and target characteristics significantly affect the method of payment choice.